Synthesis and characterization of fish scales of hydroxyapatite/collagen-silver nanoparticles composites for the applications of bone filler - Mudhafar, Mustafa; Zainol, Ismail; Alsailawi, H. A.; Jaafar, C. N. Aiza (Springer, 2021)
The most implanted tissue after blood is a bone, which consists of collagen and hydroxyapatite as the major components. Collagen is a nature-based polymer that is available in skin and tendons, whereas hydroxyapatite is a natural ceramic that is available abundantly in teeth. The composites of hydroxyapatite/collagen (HA/Col) have been reported to be the most encouraging bone graft because of the likenesses with the natural bones. Furthermore, the integration of the nano silvers in the composites’ matrix has been predicted to lead to antimicrobial reactions. This study combined the natural fish scales hydroxyapatite (FsHAp), fish scale collagen (FsCol), and nanosilver (Ag) to develop the composites of FsHAp/FsCol/nAg with various ratios of content. FTIR, XRD, EDX, and SEM were employed to identify the chemical structure and morphology of the tested composites. Similar processes were conducted to study the swelling ratio, biostability, and antibacterial features of the composites. The cytotoxicity of the FsHAp/FsCol/AgNPs composites was evaluated using Alamar blue assay. The outcome revealed that 80:20 of the HA/Col composite showed higher stability than other ratio compositions. The morphology of the composites demonstrated a homogeneous surface with nanosilvers scattered evenly in the matrix. Additionally, the activities of the antimicrobial in the composites were found against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). For the cytotoxicity study, the composites showed non-toxic effects on MG-63 human cells at high concentrations.